MÉTODOS GEOFÍSICOS APLICADOS À PROSPECÇÃO DE ÁGUA SUBTERRÂNEA, NA REGIÃO DO LAGO ARARI - PORSANI, MILTOM J.; RIJO, LUIZ; BISHOFF, JURGEN; DA FONSECA, NÉLIO RAIMUNDO M. (Águas Subterrâneas, 1980)
RESUMO NÃO DISPONÍVEL